A polyurethane composite material for bathroom and a preparation method thereof

CN122978690APending Publication Date: 2026-10-27王家祥
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611143677.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]玻纤在切割、铺层、打磨过程中产生粉尘和毛刺,导致产品表面粗糙、工人皮肤刺痒;玻纤与树脂界面仅为物理结合,热胀冷缩不匹配,长期使用或冷热循环后易分层、翘曲;玻纤铺层带入气泡,需大量腻子修补和打磨,增加人工成本

Benefits of technology

[0028]与现有技术相比,本发明的有益效果至少包括:

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a polyurethane composite material for bathroom and a preparation method thereof. The polyurethane composite material for bathroom is composed of A material and B material. The A material is composed of carbodiimide modified MDI and polymeric MDI. The B material is composed of sucrose initiator polyether, PPG, composite catalyst, molecular sieve, nano calcium carbonate, N,N'-bis(phenylmethylene)-1,2-ethylenediamine, hydrophobic modified nano silicon dioxide, silane coupling agent, defoaming agent and color paste. The raw material of the composite material does not involve styrene and glass fiber, realizes ultra-low VOC, realizes mechanical performance leap through in-situ interpenetrating network structure, can be bonded with high-strength adhesive of acryl, and completely solves the delamination problem.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, specifically to a polyurethane composite material for bathroom fixtures and its preparation method. Background Technology

[0002] Currently, the mainstream reinforcement solution in the bathroom industry (bathtubs, shower trays, sinks, and integrated bathrooms) is unsaturated polyester resin (UPR) + glass fiber (GF) hand lay-up / spray-molded fiberglass (FRP). This technical route has the following inherent defects:

[0003] (1) Styrene volatile organic compound (VOC) pollution:

[0004] Unsaturated polyester resins contain styrene at a high content of 30% to 50%, serving as a crosslinking monomer and solvent. During the molding process, a large amount of styrene volatilizes: VOC concentrations in workshops often exceed 1000 ppm, seriously endangering worker health (neurotoxicity, carcinogenicity); styrene is a flammable and explosive hazardous chemical, posing a fire and explosion hazard.

[0005] (2) Inherent defects of glass fiber:

[0006] The cutting, laying, and sanding processes of fiberglass generate dust and burrs, resulting in rough product surfaces and itchy skin for workers. The interface between fiberglass and resin is only physically bonded, and the mismatch between thermal expansion and contraction can easily lead to delamination and warping after long-term use or thermal cycling. The fiberglass layup introduces air bubbles, requiring a large amount of putty for repair and sanding, which increases labor costs.

[0007] (3) Poor adhesion to the acrylic (PMMA) surface material:

[0008] Acrylic surfaces have low polarity, and UPR / FRP and PMMA are only physically anchored together. Under humid and hot conditions, the bonding interface hydrolyzes, leading to surface delamination, bulging, cracking, and leakage. Bathroom products often experience large-area delamination after 2 to 5 years of use, which is a common quality problem in the industry. Summary of the Invention

[0009] The purpose of this invention is to provide a polyurethane composite material for bathroom products and its preparation method. The raw materials of the composite material of this invention do not involve styrene and glass fiber, achieve ultra-low VOC, and can achieve a leap in mechanical properties through an in-situ interpenetrating network structure. It can also bond with acrylic with high strength, completely solving the delamination problem.

[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0011] The first aspect of this invention provides a polyurethane composite material for bathroom use, the polyurethane composite material for bathroom use being composed of component A and component B;

[0012] Material A is composed of the following components in parts by weight:

[0013] 55-65 parts of carbodiimide-modified MDI and 35-45 parts of polymeric MDI;

[0014] Material B is composed of the following components in parts by weight:

[0015] The composition includes 40-60 parts of sucrose initiator polyether, 15-30 parts of PPG, 0.3-2 parts of composite catalyst, 2-6 parts of molecular sieve, 6-18 parts of nano-calcium carbonate, 2-6 parts of N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 1-4 parts of hydrophobically modified nano-silica, 0.5-2 parts of silane coupling agent, 0.2-1 parts of defoamer, and 0-2 parts of color paste.

[0016] Preferably, the hydroxyl value of the sucrose initiator polyether is 380~480 mgKOH / g.

[0017] Preferably, the number-average molecular weight of the PPG is 1800-4000.

[0018] Preferably, the composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether.

[0019] Preferably, the mass ratio of bismuth octanoate, zinc octanoate and bismorpholino diethyl ether is (3~5):(2~4):(1~3).

[0020] Preferably, the silane coupling agent is KH-560.

[0021] Preferably, the defoamer is BYK-088.

[0022] Preferably, the molecular sieve is a 4A molecular sieve or a 5A molecular sieve.

[0023] Preferably, the mass ratio of material A to material B is 1:(0.95~1.05).

[0024] A second aspect of the present invention provides a method for preparing the above-mentioned polyurethane composite material for bathroom fixtures, the method comprising the following steps:

[0025] (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A;

[0026] (b) The molecular sieve is activated, and then the activated molecular sieve is mixed with nano-calcium carbonate. Then, a silane coupling agent is added and stirred to obtain an activated composite filler.

[0027] (c) Add sucrose initiator polyether and PPG to the reactor and preheat and mix them. Under stirring conditions, add activated composite filler, N,N'-bis(phenylmethylene)-1,2-ethylenediamine, hydrophobically modified nano silica, composite catalyst, defoamer and color paste in sequence, and then degas under vacuum to obtain material B.

[0028] Compared with the prior art, the beneficial effects of the present invention include at least the following:

[0029] The composite material of this invention does not involve styrene and glass fiber, achieving ultra-low VOC, and can achieve a leap in mechanical properties through in-situ interpenetrating network structure, and can be bonded to acrylic with high strength, completely solving the delamination problem; specifically, this invention achieves the following through a triple reaction of "in-situ crosslinking-in-situ compatibilization-in-situ bonding" between the self-emulsifying modified MDI in material A and the polyether, molecular sieve grafted filler, and N,N'-bis(phenylmethylene)-1,2-ethylenediamine in material B: (1) in-situ interpenetrating network structure. (1) Interpenetrating network—the polyurethane crosslinked network and the N,N'-bis(phenylmethylene)-1,2-ethylenediamine network interpenetrate and lock together; (2) In-situ reinforcement—NCO grafting on the filler surface forms a chemical bond layer; (3) In-situ interface bonding—covalent bonding with the acrylic substrate is formed; This invention is free of styrene and glass fiber, with a tensile strength of up to 42.6 MPa, a peel strength from acrylic up to 5.6 kN / m, and a water absorption rate of <0.1%, which can completely replace fiberglass for bathroom structure reinforcement.

[0030] This invention activates the silanol groups on the surface of molecular sieves, allowing them to react directly with -NCO to form covalent grafts. Simultaneously, water adsorbed by the molecular sieve framework is gradually released under exothermic reaction conditions, hydrolyzing N,N'-bis(phenylmethylene)-1,2-ethylenediamine to release diamine, thus transforming water from a "harmful foaming source" into a "beneficial chain extender." Furthermore, the latent hydrolysis of N,N'-bis(phenylmethylene)-1,2-ethylenediamine releases diamine, which reacts with -NCO to form a second urea bond network. The two networks then undergo physical interpenetration and chemical cross-linking, producing a synergistic enhancement effect. Detailed Implementation

[0031] The embodiments of the technical solution of the present invention will be described in detail below with reference to the examples. The following embodiments are only used to illustrate the technical solution of the present invention more clearly, and are therefore only examples, and should not be used to limit the scope of protection of the present invention.

[0032] It should be noted that, unless otherwise stated, the technical or scientific terms used in this application should have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0033] This invention provides a polyurethane composite material for bathroom fixtures, which is composed of component A and component B.

[0034] Material A is composed of the following components in parts by weight:

[0035] 55-65 parts of carbodiimide-modified MDI and 35-45 parts of polymeric MDI;

[0036] Material B is composed of the following components in parts by weight:

[0037] The composition includes 40-60 parts of sucrose initiator polyether, 15-30 parts of PPG, 0.3-2 parts of composite catalyst, 2-6 parts of molecular sieve, 6-18 parts of nano-calcium carbonate, 2-6 parts of N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 1-4 parts of hydrophobically modified nano-silica, 0.5-2 parts of silane coupling agent, 0.2-1 parts of defoamer, and 0-2 parts of color paste.

[0038] In one embodiment, the hydroxyl value of the sucrose initiator polyether is 380~480 mgKOH / g.

[0039] In one embodiment, the number-average molecular weight of the PPG is 1800-4000.

[0040] In one embodiment, the composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether.

[0041] In one embodiment, the mass ratio of bismuth neodecanoate, zinc octanoate and bismorpholino diethyl ether is (3~5):(2~4):(1~3).

[0042] In one embodiment, the silane coupling agent is KH-560.

[0043] In one embodiment, the defoamer is BYK-088.

[0044] In one embodiment, the molecular sieve is a 4A molecular sieve or a 5A molecular sieve.

[0045] In one embodiment, the mass ratio of material A to material B is 1:(0.95~1.05).

[0046] Another embodiment of the present invention provides a method for preparing the above-mentioned polyurethane composite material for bathroom fixtures, the method comprising the following steps:

[0047] (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A;

[0048] (b) The molecular sieve is activated, and then the activated molecular sieve is mixed with nano-calcium carbonate. Then, a silane coupling agent is added and stirred to obtain an activated composite filler.

[0049] (c) Add sucrose initiator polyether and PPG to the reactor and preheat and mix them. Under stirring conditions, add activated composite filler, N,N'-bis(phenylmethylene)-1,2-ethylenediamine, hydrophobically modified nano silica, composite catalyst, defoamer and color paste in sequence, and then degas under vacuum to obtain material B.

[0050] The technical solution of the present invention will be further described in detail below through specific embodiments.

[0051] The raw materials used in the following embodiments are as follows:

[0052] Carbodiimide-modified MDI: CDMDI-100L, brand Wanhua;

[0053] Polymer MDI: PM-200, brand Wanhua;

[0054] Sucrose initiator polyether: H4110, Red Poly;

[0055] PPG: PPG-2000;

[0056] Silane coupling agent: KH-560;

[0057] Defoamer: BYK-088;

[0058] Molecular sieve: 4A molecular sieve;

[0059] Example 1

[0060] This embodiment is a polyurethane composite material for bathroom use, which is composed of component A and component B; the mass ratio of component A to component B is 1:0.95;

[0061] Material A is composed of the following components in parts by weight:

[0062] 55 parts of carbodiimide-modified MDI and 45 parts of polymeric MDI;

[0063] Material B is composed of the following components in parts by weight:

[0064] The composition includes 40 parts of sucrose initiator polyether, 30 parts of PPG, 0.3 parts of composite catalyst, 6 parts of molecular sieve, 6 parts of nano-calcium carbonate, 6 parts of N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 1 part of hydrophobically modified nano-silica, 2 parts of silane coupling agent, and 0.2 parts of defoamer.

[0065] The composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether; the mass ratio of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether is 3:2:1.

[0066] The preparation method of the above-mentioned polyurethane composite material for bathroom fixtures includes the following steps:

[0067] (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A;

[0068] (b) The molecular sieve was calcined at 350°C for 2 hours, and then the activated molecular sieve was mixed with nano-calcium carbonate. Then, a silane coupling agent was added and stirred to obtain the activated composite filler.

[0069] (c) Add the sucrose initiator polyether and PPG to the reactor and preheat until mixed. Under stirring conditions, add the activated composite filler at 700 rpm for 20 min, N,N'-bis(phenylmethylene)-1,2-ethylenediamine for 10 min, hydrophobically modified nano silica for 10 min, composite catalyst for 10 min, defoamer and color paste for 5 min, and then degas under vacuum to obtain material B.

[0070] Example 2

[0071] This embodiment is a polyurethane composite material for bathroom use, which is composed of component A and component B; the mass ratio of component A to component B is 1:1.05;

[0072] Material A is composed of the following components in parts by weight:

[0073] 65 parts of carbodiimide-modified MDI and 35 parts of polymeric MDI;

[0074] Material B is composed of the following components in parts by weight:

[0075] The ingredients are: 60 parts sucrose initiator polyether, 15 parts PPG, 2 parts composite catalyst, 2 parts molecular sieve, 18 parts nano calcium carbonate, 2 parts N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 4 parts hydrophobically modified nano silica, 0.5 parts silane coupling agent, 1 part defoamer, and 2 parts titanium dioxide.

[0076] The composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether; the mass ratio of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether is 5:4:3.

[0077] The preparation method of the above-mentioned polyurethane composite material for bathroom fixtures includes the following steps:

[0078] (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A;

[0079] (b) The molecular sieve was calcined at 350°C for 2 hours, and then the activated molecular sieve was mixed with nano-calcium carbonate. Then, a silane coupling agent was added and stirred to obtain the activated composite filler.

[0080] (c) Add the sucrose initiator polyether and PPG to the reactor and preheat until mixed. Under stirring conditions, add the activated composite filler at 700 rpm for 20 min, N,N'-bis(phenylmethylene)-1,2-ethylenediamine for 10 min, hydrophobically modified nano silica for 10 min, composite catalyst for 10 min, defoamer and color paste for 5 min, and then degas under vacuum to obtain material B.

[0081] Example 3

[0082] This embodiment is a polyurethane composite material for bathroom use, which is composed of component A and component B; the mass ratio of component A to component B is 1:1.

[0083] Material A is composed of the following components in parts by weight:

[0084] 60 parts of carbodiimide-modified MDI and 40 parts of polymeric MDI;

[0085] Material B is composed of the following components in parts by weight:

[0086] The ingredients are: 50 parts sucrose initiator polyether, 20 parts PPG, 1 part composite catalyst, 4 parts molecular sieve, 12 parts nano calcium carbonate, 4 parts N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 3 parts hydrophobically modified nano silica, 1 part silane coupling agent, 0.5 parts defoamer, and 1 part titanium dioxide.

[0087] The composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether; the mass ratio of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether is 4:3:2.

[0088] The preparation method of the above-mentioned polyurethane composite material for bathroom fixtures includes the following steps:

[0089] (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A;

[0090] (b) The molecular sieve was calcined at 350°C for 2 hours, and then the activated molecular sieve was mixed with nano-calcium carbonate. Then, a silane coupling agent was added and stirred to obtain the activated composite filler.

[0091] (c) Add the sucrose initiator polyether and PPG to the reactor and preheat until mixed. Under stirring conditions, add the activated composite filler at 700 rpm for 20 min, N,N'-bis(phenylmethylene)-1,2-ethylenediamine for 10 min, hydrophobically modified nano silica for 10 min, composite catalyst for 10 min, defoamer and color paste for 5 min, and then degas under vacuum to obtain material B.

[0092] Comparative Example 1

[0093] This comparative example is a polyurethane composite material for bathroom use, which is basically the same as the polyurethane composite material for bathroom use in Example 3, except that N,N'-bis(phenylmethylene)-1,2-ethylenediamine was not added.

[0094] The preparation method of the above-mentioned polyurethane composite material for bathroom use is the same as that in Example 3.

[0095] Comparative Example 2

[0096] This comparative example is a polyurethane composite material for bathroom use. The polyurethane composite material for bathroom use is basically the same as the polyurethane composite material for bathroom use in Example 3, except that no molecular sieve is added.

[0097] The preparation method of the above-mentioned polyurethane composite material for bathroom products is the same as that in Example 3.

[0098] Comparative Example 3

[0099] This comparative example is a polyurethane composite material for bathroom use. The polyurethane composite material for bathroom use is basically the same as the polyurethane composite material for bathroom use in Example 3, except that carbodiimide-modified MDI is replaced with an equal amount of polymeric MDI.

[0100] The preparation method of the above-mentioned polyurethane composite material for bathroom products is the same as that in Example 3.

[0101] Comparative Example 4

[0102] This comparative example is a polyurethane composite material for bathroom use. The polyurethane composite material for bathroom use is basically the same as the polyurethane composite material for bathroom use in Example 3, except that the sucrose initiator polyether is replaced with an equal amount of PPG.

[0103] The preparation method of the above-mentioned polyurethane composite material for bathroom products is the same as that in Example 3.

[0104] Experimental Example

[0105] The polyurethane composite materials for bathroom use prepared in Example 3 and Comparative Examples 1-4 were obtained respectively;

[0106] Preheat components A and B of the polyurethane composite material for bathroom fixtures to 25-30℃ respectively;

[0107] Mixing: A:B is measured at a mass ratio of 1:1 and mixed for 15~30s using a high-speed dynamic mixing device (≥3000rpm);

[0108] On the back of acrylic bathroom products, the coating is completed during the mixing process; the coating thickness is 5mm, cured, and the edge burrs are trimmed after demolding.

[0109] The mechanical properties, water absorption rate, adhesion strength to acrylic, and complete curing time of the above coating were tested, and the results are shown in Table 1.

[0110] Table 1

[0111] project Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength (MPa) 42.6 24.8 28.3 30.5 16.4 Bending strength (MPa) 61.3 38.2 42.7 45.7 28.6 <![CDATA[Impact strength (KJ / m 2 )]]> 11.4 6.5 8.8 9.2 12.8 Water absorption rate (24h, %) 0.08 0.35 0.52 0.15 0.12 Acrylic peel strength (kN / m) 5.6 2.9 4.1 4.2 3.5 Complete curing (min) 55 35 55 60 75

[0112] As shown in Table 1:

[0113] Compared with the comparative example, the polyurethane composite material for bathroom use prepared in the embodiments of the present invention has superior performance.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A polyurethane composite material for bathroom fixtures, characterized in that, The polyurethane composite material for bathroom use is composed of component A and component B; Material A is composed of the following components in parts by weight: 55-65 parts of carbodiimide-modified MDI and 35-45 parts of polymeric MDI; Material B is composed of the following components in parts by weight: The composition includes 40-60 parts of sucrose initiator polyether, 15-30 parts of PPG, 0.3-2 parts of composite catalyst, 2-6 parts of molecular sieve, 6-18 parts of nano-calcium carbonate, 2-6 parts of N,N'-bis(phenylmethylene)-1,2-ethylenediamine, 1-4 parts of hydrophobically modified nano-silica, 0.5-2 parts of silane coupling agent, 0.2-1 parts of defoamer, and 0-2 parts of color paste.

2. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The hydroxyl value of the sucrose initiator polyether is 380~480 mgKOH / g.

3. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The number-average molecular weight of the PPG is 1800~4000.

4. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The composite catalyst is composed of bismuth neodecanoate, zinc octanoate, and bismorpholino diethyl ether.

5. The polyurethane composite material for bathroom fixtures according to claim 4, characterized in that, The mass ratio of the bismuth octanoate, zinc octanoate and bismorpholino diethyl ether is (3~5):(2~4):(1~3).

6. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The silane coupling agent is KH-560.

7. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The defoamer is BYK-088.

8. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The molecular sieve is a 4A molecular sieve or a 5A molecular sieve.

9. The polyurethane composite material for bathroom fixtures according to claim 1, characterized in that, The mass ratio of material A to material B is 1: (0.95~1.05).

10. The method for preparing the polyurethane composite material for sanitary ware according to any one of claims 1 to 9, characterized in that, The preparation method includes the following steps: (a) Carbodiimide-modified MDI and polymeric MDI were stirred and mixed under a nitrogen atmosphere to obtain material A; (b) The molecular sieve is activated, and then the activated molecular sieve is mixed with nano-calcium carbonate. Then, a silane coupling agent is added and stirred to obtain an activated composite filler. (c) Add sucrose initiator polyether and PPG to the reactor and preheat and mix them. Under stirring conditions, add activated composite filler, N,N'-bis(phenylmethylene)-1,2-ethylenediamine, hydrophobically modified nano silica, composite catalyst, defoamer and color paste in sequence, and then degas under vacuum to obtain material B.